2017
DOI: 10.3354/meps12042
|View full text |Cite
|
Sign up to set email alerts
|

High levels of solar radiation offset impacts of ocean acidification on calcifying and non-calcifying strains of Emiliania huxleyi

Abstract: Coccolithophores, a globally distributed group of marine phytoplankton, showed diverse responses to ocean acidification (OA) and to combinations of OA with other environmental factors. While their growth can be enhanced and calcification be hindered by OA under constant indoor light, fluctuation of solar radiation with ultraviolet irradiances might offset such effects. In this study, when a calcifying and a non-calcifying strain of Emiliania huxleyi were grown at 2 CO 2 concentrations (low CO 2 [LC]: 395 µatm;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 53 publications
4
22
1
Order By: Relevance
“…For instance, when three diatom species were grown under different levels of sunlight, lowered pH with elevated CO 2 stimulated growth under low to moderate levels of light, but inhibited it under high levels (Gao et al, 2012a; Figure 3). However, such a reversed response to OA with increasing light levels was not found in coccolithophores, which showed enhanced growth rates (with reduced calcification) under the elevated pCO 2 under all tested PAR levels (Jin et al, 2017; FIGURE 3 | A schematic representation of the differing relationship between sunlight intensity and the growth rates of diatoms (A) and coccolithophores (B) grown at low (390 µatm, blue lines) and high (1,000 µatm, red lines) CO 2 concentrations, respectively. Note that elevated CO 2 stimulates growth in diatoms at low light but inhibits them at high light levels.…”
Section: Oa and Solar Radiation (Par And Uvr)mentioning
confidence: 76%
“…For instance, when three diatom species were grown under different levels of sunlight, lowered pH with elevated CO 2 stimulated growth under low to moderate levels of light, but inhibited it under high levels (Gao et al, 2012a; Figure 3). However, such a reversed response to OA with increasing light levels was not found in coccolithophores, which showed enhanced growth rates (with reduced calcification) under the elevated pCO 2 under all tested PAR levels (Jin et al, 2017; FIGURE 3 | A schematic representation of the differing relationship between sunlight intensity and the growth rates of diatoms (A) and coccolithophores (B) grown at low (390 µatm, blue lines) and high (1,000 µatm, red lines) CO 2 concentrations, respectively. Note that elevated CO 2 stimulates growth in diatoms at low light but inhibits them at high light levels.…”
Section: Oa and Solar Radiation (Par And Uvr)mentioning
confidence: 76%
“…Phytoplankton use several mechanisms to repair UVinduced damage, many of which involve nitrogen-requiring enzymes and/or protein cofactors (Litchman et al, 2002). Korbee et al (2010) reported that UVA could stimulate algae nitrogen metabolism (nitrate transport and reductase activity). In contrast, UVB was found to damage cell membranes and negatively affect nitrogen incorporation mechanisms, leading to an increase in the C / N ratio (Sobrino et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Increased light supply to E. huxleyi has recently shown to decrease the inhibitory effects of OA on its calcification (Jin et al. ).…”
Section: Discussionmentioning
confidence: 99%